Transition length of two stationary random functions in investigation of railway stability - Nam, Nguyen Duong (Vietnam Journal of Mechanics, 2000)
In this paper the scientific justification for determination of transition length of two stationary random functions is presented on the basis of the weight function and properties of stationary random function in wide sense. The application of the results for practice gives the transition lengths of straight and curved railway, which it is necessary to throw away in measurement of initial horizontal displacement of railway in its stability estimation under action of longitudinal compression load.